Study of Characteristic Strength of Concrete by Partial Replacing Cement with Ceramic Waste Powder - Harikrishna Chaudhry; Mr. Rahul Kumar Satbhaiya (International Journal of Scientific Research in Civil Engineering, 2025)
In the construction sector, ceramic wall tiles are commonly employed as essential building materials. These tiles are manufactured using a combination of raw substances such as clay, feldspar, dolomite, potash, talc, and chemical additives like sodium silicate, sodium tripolyphosphate (STPP), and others. The manufacturing process involves firing at varying temperatures, typically ranging from 200°C to 1200°C, which imparts pozzolanic properties to the material. During the tile manufacturing process, approximately 5–10% of the total production results in waste, although this figure can be reduced with the implementation of modern technologies in newer plants. Improper disposal of this ceramic waste often leads to environmental degradation, especially when dumped near agricultural lands, affecting both the ecosystem and nearby communities. It not only minimizes waste disposal issues and conserves natural resources by partially substituting raw materials but also contributes to lowering carbon emissions associated with cement manufacturing, a major source of CO₂. This study investigates the use of ceramic waste powder derived from the ceramic tile industry, in combination with hydraulic lime, as a partial replacement for cement in M25 grade concrete. The replacement was done incrementally at proportions of 0%, 10%, 20%, 25%, 30%, and 40% by weight of cement to evaluate its impact on concrete performance and sustainability.